2020
DOI: 10.1155/2020/8889061
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Neurodegenerative Diseases: How Do Stem Cells Bypass the Blood-Brain Barrier and Home to the Brain?

Abstract: Blood-brain barrier (BBB) is a term describing the highly selective barrier formed by the endothelial cells (ECs) of the central nervous system (CNS) homeostasis by restricting movement across the BBB. An intact BBB is critical for normal brain functions as it maintains brain homeostasis, modulates immune cell transport, and provides protection against pathogens and other foreign substances. However, it also prevents drugs from entering the CNS to treat neurodegenerative diseases. Stem cells, on the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 83 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…However, the blood-spinal cord barrier is disrupted for weeks in contusion SCI models [287]. These findings show there is no evidence that stem cells cross the BBB as discussed in a recent review [288]. Early work examined the distribution of stem cells in brain after IV injection, and observed that no stem cells were detected in brain parenchyma, although stem cells invade the meninges of brain [289], where there is no BBB.…”
Section: Stem Cells For Brain Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the blood-spinal cord barrier is disrupted for weeks in contusion SCI models [287]. These findings show there is no evidence that stem cells cross the BBB as discussed in a recent review [288]. Early work examined the distribution of stem cells in brain after IV injection, and observed that no stem cells were detected in brain parenchyma, although stem cells invade the meninges of brain [289], where there is no BBB.…”
Section: Stem Cells For Brain Drug Deliverymentioning
confidence: 99%
“…• Stem cells do not cross the BBB [288], nor enter brain parenchyma [289] as reviewed in Section 5.1.…”
Section: Stem Cell Delivery To Brainmentioning
confidence: 99%
“…It is therefore worthwhile to consider further exploration regarding the use of stem cells as new and effective means to interfere with GWI disease and its progression. It is known that stem cells can successfully home to their target in the brain and initiate repair, making them a promising approach in cellular therapy in neurodegenerative diseases including GWI 20 . Possible sources of self-derived MSC in adult subjects include the bone marrow and fat tissue 18 ; Stem cells from these sources could be used in order to establish their protective effect in vivo in GWI.…”
Section: Discussionmentioning
confidence: 99%
“…They reduce encephalitis and recover the blood-brain barrier (BBB) in the brain. 56 In gut, they can regulate inflammation, remodel tissue, and promote the eradication of infections (Figure 1). 20 -3 of 14 H7N9) have provided promising hope in the fight against COVID-19.…”
Section: Therapeutic Effects Of Mscsmentioning
confidence: 99%